2022
DOI: 10.3390/land11111999
|View full text |Cite
|
Sign up to set email alerts
|

Has China’s Pilot Policy of Water Ecological Civilization City Construction Reduced Water Pollution Intensity?

Abstract: To address the deterioration of the water ecological environment, China’s Ministry of Water Resources launched 105 pilot projects for the construction of water ecological civilized cities in two batches in 2013 and 2014. Based on panel data of 283 cities in China from 2008 to 2020, in this study, we investigate the impact of the pilot policy of water ecological civilization city construction on water pollution intensity using the difference-in-differences method. We found that water pollution intensity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Through in-depth research on the impact of CCC on EGI, we can provide reference and guidance for enterprises and governments to promote the realization of the goals of sustainable development and environmental protection [31]. Second, this study introduces CCC as a research object, which expands the research perspective on the mechanism of urban governance policy's influence on corporate behavior, and has a certain degree of research innovation [30]. The results of the study show that CCC promotes EGI by strengthening environmental regulation efforts and increasing environmental subsidies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Through in-depth research on the impact of CCC on EGI, we can provide reference and guidance for enterprises and governments to promote the realization of the goals of sustainable development and environmental protection [31]. Second, this study introduces CCC as a research object, which expands the research perspective on the mechanism of urban governance policy's influence on corporate behavior, and has a certain degree of research innovation [30]. The results of the study show that CCC promotes EGI by strengthening environmental regulation efforts and increasing environmental subsidies.…”
Section: Discussionmentioning
confidence: 95%
“…Its evaluation methods and assessment systems are also more stringent, exerting greater constraints on enterprises [29]. Particularly, the assessment system incorporates selection and review mechanisms, prompting local governments to enhance supervision and governance measures for enterprises to win the evaluation [30,31]. However, the existing research does not conclusively determine whether this policy can promote enterprise environmental behavior and enhance green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…This integrated approach reflects a balanced relationship between environmental protection and economic benefits under a differentiated sewage treatment fee system. Therefore, it is suggested that different regions adopt different sewage treatment fee collection standards based on their respective economic development levels and current environmental quality conditions [78][79][80][81], whereby higher pollution would lead to higher fees.…”
Section: Implementing a Differentiated Sewage Treatment Fee Collectio...mentioning
confidence: 99%
“…Sustainable development is the way of the future for human advancement, but one of the main obstacles to it is environmental pollution, which is caused by the reckless discharge of various toxins into the environment and the wasteful use of natural resources (Ahmed et al., 2022). Water is a crucial resource for human social development and the health of ecological systems, but heavy metal pollution (Yuan et al., 2021), organic pollution, thermal pollution, and eutrophication in the water environment seriously endanger people's health, the wellbeing of wildlife, and the security of water bodies (Gupta et al., 2022; Lyu et al., 2022). In order to create acceptable and efficient water environmental protection measures as well as pollution prevention measures that will help to restrict the growth of water pollution in both domestic and international contexts, accurate information of the water quality of water bodies is a prerequisite (Agbasi & Egbueri, 2022).…”
Section: Introductionmentioning
confidence: 99%